Diversity and abundance of flower visitors in rapeseed (Brassica napus L.) and spontaneous Brassicaceae: effects on crop yield in the southern Pampas region - Marinozzi Luciano Alberto; Villamil Soledad Camila; Gallez Liliana María (Oilseeds and fats, crops and lipids)
Conservation of biodiversity in agroecosystems is essential for the sustainability of insect-pollinated crops. This study aimed to evaluate the importance of areas near the rapeseed crops containing spontaneous Brassicaceae species and to identify the insects visiting both. We assessed the impact of pollinators on rapeseed yield, its components, and seed oil content. The research was conducted in experimental plots in the southeastern Pampas region during 2017, 2018, and 2019. Each year, two rapeseed cultivars (a hybrid and a variety) were tested. The flowering period of spontaneous Brassicaceae extended beyond 90 days, approximately three times longer than the rapeseed crop. In the spontaneous Brassicaceae and the rapeseed plots, the same species of flower visitors were captured. However, in two of the three years, the number of insects was higher in the spontaneous patches. These findings highlight the importance of these plants as food resources for pollinators. When insects had access to the crop, the yield was significantly higher for all tested rapeseed cultivars, with an average increase ranging between 27% and 35%. Pollinators enhanced rapeseed production without affecting the oil percentage, resulting in an increased oil yield per hectare by positively impacting grain yield.